The Workshop: A Format and Promise Between Collectivity and Individualism - Hölscher, Stefan (Peripeti, 2020)
This essay investigates how far the contemporary phenomenon of the workshop in the dance field can be contrasted to the historical emergence of the workshop format in the context of the Neo-Avantgardes during the 1960s. It suggests that contemporary ways of hanging out together should be situated in the area of conflict between the group and the self.